Police officers giving evidence: Discussing gaps, contradictions and next steps. (June 2017) - Brian, David; Cruickshank, Andrew
This article reviews Police Research Series Paper 15, The Presentation of Police Evidence in Court (Stockdale and Gresham, 1995), and the role of police officers giving testimony in court. In particular, consideration is given to the recommendations made and subsequent developments, or lack thereof, in police literature and practice. Police officers are well prepared to manage the pre-trial investigation but still receive little preparation, or guidance from researchers, for performing as witnesses at court. Key factors in effectively presenting evidence are reviewed and directions outlined for building knowledge on preparing police officers to perform in court whilst upholding obligation to victims and the legal standard of public interest.